Pelatihan Fotografi Produk untuk Meningkatkan Kreativitas dan Daya Saing di Era Digital - Adit, Ambar Aditya Putra; Yan Aditiya Pratama (Penerbit Goodwood, 2025)
Purpose: The Product Photography Training aims to equip students with practical skills relevant to the creative industry's growth in the digital era. It focuses on developing both basic and advanced photography techniques, enabling students to produce visually appealing and marketable content. Beyond technical proficiency, the program fosters creativity, critical thinking, and innovation in visual expressions. Methodology/approach: The program was conducted in four key stages: preparation, implementation, evaluation, and follow-up. The preparation involved school coordination, needs assessment, and development of training materials. The implementation stage delivered theoretical and hands-on training covering camera operation, lighting, and composition. Evaluation was conducted through participant work assessments, engagement tracking, quizzes, and pre- and post-program surveys and interviews. Results/findings: The training significantly improved students’ understanding of product photography, digital content creation and visual marketing strategies. The participants successfully produced quality product images and applied them to promotional content aligned with market trends. The program also enhanced students’ 4Cs—critical thinking, creativity, communication, and collaboration—through real-world visual media application. Conclutions: Training at SMA Negeri 15 Bandar Lampung effectively enhanced students' skills and creativity in product photography. It provides practical experience that supports students’ readiness for the creative industry and contributes to character development in the digital era. Limitations: The program's short duration and limited participant pool restricted the generalizability of the results. The long-term impacts were not assessed. Contribution: This study contributes to educational practice by demonstrating how photography training can develop relevant skills and creativity in students in the context of digital and creative industries.